Formulasi Nugget Ikan Tongkol Berbasis Ampas Jagung sebagai Sumber Protein PMT Lokal - Tasniatul Niswa Niswa; Muh. Aniar Hari Swasono Swasono (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
Tuna fish nuggets are a type of processed food product based on animal protein that holds significant potential as a functional food to help prevent stunting in children. This study employed a Completely Randomized Design with 5 treatment formulations involving different ratios of tuna meat to corn residue, each replicated 3 times. The analyses conducted included chemical tests (moisture, ash, fat, protein, and carbohydrate content), physical tests (texture), and organoleptic tests (color, aroma, and taste). Statistical analysis was performed using Analysis of Variance (ANOVA) and Tukey’s test at a 95% significance level, using Minitab software. The physicochemical test results of the tuna fish nuggets showed ash content ranging from 0.70% to 2.53%, moisture content from 57.30% to 62.88%, protein content from 4.10% to 8.80%, fat content from 11.43% to 20.60%, carbohydrate content from 8.21% to 20.87%, and texture values from 17.37 to 22.87 N. Sensory evaluation results indicated aroma scores between 3.76 and 4.48, taste between 3.72 and 4.48, and color between 3.44 and 4.24. The best formulation was obtained from treatment P1 (250 grams tuna meat: 50 grams corn residue), which yielded a moisture content of 62.88%, ash 0.70%, fat 20.60%, protein 8.80%, carbohydrate 8.21%, and texture 25.26 N. In terms of sensory attributes, color scored 3.76, aroma 4.12, and taste 4.20, all of which fall into the “liked” category according to panelist evaluations.